Por uma racionalização das políticas legislativas criminais: o dilema entre a expansão do direito penal e a necessidade de proteção de novos bens jurídicos - Ismael, Marcelo Castelo Branco (Universidade do Vale do Rio dos Sinos, 2014)
This research aims to examine the necessity and rationality of the expansion of criminal law in the face of new legal protection of property. This objective will be accomplished by means of a dialogue between the ideas of Claus Roxin and Gunther Jakobs about the fundamentals and purposes of criminal law. According to Roxin, criminal law should be used as a protection of essential interests legal to the full development and existence of a state. On the other hand, Gunther Jakobs argues that the criminal law is intended to ensure the validity of the standard. In the first chapter discussed the expansion of criminal law, its meaning, motives, purposes and concrete examples, for both will be treated based on the society's risk and the spread of fear towards risk and the role of society as a driver and victim of this expansion legislating. In the second chapter will be check the legislative rationality criminal of such expansive movement, especially in the pre-legislative's phase opposite generating social dysfunction thoughtless criminal expansion. A concept of rationality, that will be presented still being made an approach to theories that legitimize the penalty in order to be shown that the criminal expansive movement goes against the founding principles of criminal law, as the minimum intervention, subsidiarity, creating symbolic's and ineffective tupes, after a brief analysis of the principles governing the criminal law. In the third chapter will be presents the concept of good legal, the new poor legal interests of penal law. As also discussed the real purpose of criminal law in the face of the protection of legal interests, performing a dialogue between the functionalist theories by Roxin and Jakobs, presented on the rational point of each. The method used is the phenomenological's hermeneutic through at literature search, the end being shown that the function of criminal law goes beyond protecting legal interests or the validity of the standard, it is actually a limit to the discretion and delimiter of a welfare state democratic rights.
Keywords: Racionalidade; Expansão do direito penal; Bens jurídicos; Expansion; Criminal law; Rationality; Legal interests; ACCNPQ::Ciências Sociais Aplicadas::Direito